2018
DOI: 10.1016/j.fertnstert.2018.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Role of medical therapy in the management of uterine adenomyosis

Abstract: Adenomyosis is a benign uterine condition affecting women at various ages with different symptoms. The management of these patients is still controversial. Few clinical studies focusing on medical or surgical treatment for adenomyosis have been performed. No drug is currently labelled for adenomyosis and there are no specific guidelines to follow for the best management. Anyhow, medical treatments are effective in improving symptoms (pain, abnormal uterine bleeding and infertility). The rationale for using med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
171
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(196 citation statements)
references
References 94 publications
(89 reference statements)
2
171
0
2
Order By: Relevance
“…In the present study, we found that mifepristone reduces the secretion of IL-6 and TNF-α from endometrial epithelial and stromal cells in adenomyosis. Similar to MPA and danazol treatment of adenomyosis [32,33], mifepristone treatment inhibited the secretion of IL-6 in endometrial epithelial and stromal cells of adenomyosis in our experiments. Yang et al reported that MPA and danazol have no effect on the suppression of TNF-α by endometrial and stromal cells in adenomyosis [34] while our data showed mifepristone significantly decreased the mRNA and protein expression of TNF-α in both endometrial epithelial and stromal cells of adenomyosis.…”
Section: Discussionsupporting
confidence: 77%
“…In the present study, we found that mifepristone reduces the secretion of IL-6 and TNF-α from endometrial epithelial and stromal cells in adenomyosis. Similar to MPA and danazol treatment of adenomyosis [32,33], mifepristone treatment inhibited the secretion of IL-6 in endometrial epithelial and stromal cells of adenomyosis in our experiments. Yang et al reported that MPA and danazol have no effect on the suppression of TNF-α by endometrial and stromal cells in adenomyosis [34] while our data showed mifepristone significantly decreased the mRNA and protein expression of TNF-α in both endometrial epithelial and stromal cells of adenomyosis.…”
Section: Discussionsupporting
confidence: 77%
“…However, no drug is currently labeled for adenomyosis, and there are no specific guidelines to follow for best management. [ 13 ] Two important observations can be made from this study. First, GnRHa therapy significantly reduced the volume of adenomyosis, while LEP or DNG therapy resulted in neither a significant reduction nor increase in uterine volume.…”
Section: Discussionmentioning
confidence: 75%
“…5 Adenomyosis symptoms can be disabling and have been treated medically, despite no U.S. Food and Drug Administrationeapproved therapies, 1 and surgically. 7 Better data on efficacy of medical treatment would assist women who prefer not to have hysterectomy. Tools that can track adenomyosis incidence, prevalence, and treatment response will be important as new therapies targeted at the pathogenesis of the disease-sex steroid regulation, inflammation, apoptosis, and neuroangiogenesis manipulation 7,8 are developed.…”
mentioning
confidence: 99%